PROJECTILE MOTION OF A CRICKET BALL FROM BOWLING TO OVER BOUNDARY IN CRICKET - Maitra, S. N. (SCHOOL SCIENCE, 2014)
In a cricket game, bowler bowls at the batsman who hits the ball powerfully and hits an over boundary. In this process, first considered projectile motion of the ball from the bowler to the pitch where the ball strikes affecting an elastic impact with the grounds followed by its second projectile motion until being batted by the batsman causing the second impact but between the ball and the bat. The third projectile motion arises from the batsman to a spot outside the field resulting in score of an over boundary, So that in course of projectile motion of the cricket ball vis-a-vis its impact with the pitch and the bat a minimum velocity of hitting the ball with the bat by the batsman for over boundary is determined. Thereafter the maximum range in the horizontal direction of the ball due to a given velocity of hitting it, escaping a catch by a fieldsman, is also computed. All along the air resistance is neglected. The effects of spinning of the ball are neglected